Assessment of energy technologies in electricity and transport sectors based on carbon intensity and costs - Štreimikienė, Dalia (Technological and Economic Development of Economy, 2013)
The aim of the paper is to address the EU policy for achieving low carbon economy by assessing energy technologies in electricity and road transport sector based on costs and impact on climate change and to indicate the most competitive electricity and transport technologies taking into account EU policy targets in GHG emission reduction, utilization of renewable and energy efficiency improvements. The main tasks of the paper are: to develop the multi-criteria framework for comparative assessment of energy technologies by applying MCDM methods for the electricity generation and transport technologies assessment. The interval TOPSIS method is employed in order to tackle the uncertain criteria. The assessment framework allows the comparison of electricity generation technologies and road transport technologies in terms of their GHG emission reduction and economic impacts and facilitates decision making process in energy sector seeking to implement EU energy policies. The main indicators selected for technologies assessment are: private costs and life cycle GHG emissions. The ranking of energy technologies based on private costs and GHG emissions allowed prioritizing these technologies taking into account the lowest GHG emission reduction costs.